Analysis on Cracking Reasons of U - Type Parts Used in Subway - CHEN Liang, LIU Li, YAO Liang, XU Hao - jie (Cailiao Baohu, 2021)
Some cracks were found on the surface of U - type parts which had been at the service of subway for several years, and the cracking reason of U - type parts was analyzed by means of macroscopic analysis, chemical composition analysis, non - metallic inclusion content determination, SEM and EDS examination, and metallographic test. Results showed that the material of U - type parts was 302 austenite stainless steel, which was easy to precipitate carbides at the grain boundary to produce the chromium depleted region near the grain boundary, causing intergranular corrosion, and the corroded grain boundary acts as the crack source, then stress corrosion cracking occurred under the combined effect of Cl- and external force as the running time of parts increased.